2000
DOI: 10.1111/j.1532-5415.2000.tb02646.x
|View full text |Cite
|
Sign up to set email alerts
|

Can the Control of Bodily Orientation Be Significantly Improved in a Group of Older Adults with a History of Falls?

Abstract: Theory-driven rehabilitation programs that focus on manipulating individual, task, and environmental constraints concurrently can significantly improve the control of bodily orientation of older adults with a previous history of falls in both static and dynamic action environments. Moreover, the significant improvements in functional performance observed for the intervention group suggest that interventions emphasizing task-specific practice are not the only means by which an older adult's ability to perform d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 22 publications
6
56
0
4
Order By: Relevance
“…Concurrent augmented visual feedback has also been applied to re-learning balancing tasks among individuals with impaired balance due to neurologic injury (Shumway-Cook et al 1988;Winstein et al 1989;Sackley and Lincoln 1997;Walker et al 2000;Ioffe et al 2010;Sayenko et al 2010;Tsaklis et al 2012) or aging (Wolf et al 1997;Rose and Clark 2000;Lajoie 2004;Sihvonen et al 2004b;Hatzitaki et al 2009). Typically, this is done by asking the participant to stand on one or two force platforms and providing visual feedback regarding weight distribution between the two limbs (Winstein et al 1989;Sackley and Lincoln 1997;Hatzitaki et al 2009), or the location of the centre of gravity (COG; Rose and Clark 2000;Walker et al 2000) or centre of pressure (COP; Shumway-Cook et al 1988;Lajoie 2004;Sihvonen et al 2004b;Ioffe et al 2010;Sayenko et al 2010;Tsaklis et al 2012). With the goal of improving quiet standing balance control when provided with feedback of the COG or COP, participants are asked to minimize movement of the COG or COP (Shumway-Cook et al 1988;Lajoie 2004;Sayenko et al 2010;Tsaklis et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent augmented visual feedback has also been applied to re-learning balancing tasks among individuals with impaired balance due to neurologic injury (Shumway-Cook et al 1988;Winstein et al 1989;Sackley and Lincoln 1997;Walker et al 2000;Ioffe et al 2010;Sayenko et al 2010;Tsaklis et al 2012) or aging (Wolf et al 1997;Rose and Clark 2000;Lajoie 2004;Sihvonen et al 2004b;Hatzitaki et al 2009). Typically, this is done by asking the participant to stand on one or two force platforms and providing visual feedback regarding weight distribution between the two limbs (Winstein et al 1989;Sackley and Lincoln 1997;Hatzitaki et al 2009), or the location of the centre of gravity (COG; Rose and Clark 2000;Walker et al 2000) or centre of pressure (COP; Shumway-Cook et al 1988;Lajoie 2004;Sihvonen et al 2004b;Ioffe et al 2010;Sayenko et al 2010;Tsaklis et al 2012). With the goal of improving quiet standing balance control when provided with feedback of the COG or COP, participants are asked to minimize movement of the COG or COP (Shumway-Cook et al 1988;Lajoie 2004;Sayenko et al 2010;Tsaklis et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rose and Clark implemented an 8-week balance intervention with computerized biofeedback training for older fallers and measured the dynamic postural control and sensory organization before and after balance training [26]. The dynamic balance and sensory integration capabilities of the intervention group improved significantly, indicating that rehabilitation programs could concurrently and significantly improve the control of bodily orientation of older adults with a previous history of falls in both static and dynamic action environments [26]. Sihvonen et al examined the effects of 4-week visual-feedback-based balance training on the fall incidence during a 1-year follow-up among frail older women living in residential care [27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, however, have reported on the correlation between balance training and visual external feedback. This training was used to improve the dynamic balance and sensory integration capabilities of elderly adults with a history of falls [26] and was helpful for frail older women [27] and elderly women living in residential care [28]. It also has been preferred to home-based balance training [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach differs from existing educational interventions for the elderly which are either more reactive in their approach and/or focus on specific types of problems the elderly may already experience; for example, reducing loneliness, depression and physical limitations (e.g. [9,10]), improving physical activation and mobility of sedentary older adults or addressing risk behaviours such as high risk driving, decreasing communication skills, overweight and poor nutrition (e.g. [11][12][13]).…”
Section: Introductionmentioning
confidence: 99%